Control Volume Analysis of Unsteady Mhd Mixed Convection Nanofluid Flow as A Result of Stretching Surface with Suction - Kitetu, Virginia M.; Onyango, Thomas T. M.; Kwanza, Jackson K. (MksU Press, 2021)
Many heat transfer processes in engineering problems in areas such as nuclear reactors and electronics, as well as in biomedicine and food industry require the knowledge of nanofluids. Consequently, investigations leading to understanding of the role played by nanofluids in heat transfer enhancement in these processes is vital. Currently, numerous studies are being conducted on nanofluids for the benefits associated with low energy costs and less negative environmental impact in industry and society. In the studies, water is commonly used as base for nanofluids in heat transfer applications due to its ability and availability for heat transport. In most of these investigations influence of nanoparticles have been analyzed to determine enhancement of energy transfer on stretched sheets. In this research, magnetohydrodynamic mixed convection flow of a nanofluid over a stretching sheet with water equally as the base fluid and either Copper or Silver as nanoparticles is examined anddiscussed. The physical problem is modeled using systems of unsteady nonlinear differential equations (DE) subject to prescribed boundary and initial conditions, which are then studied using Finite volume approach. These DE comprise of the classical continuity, momentum, concentration and energy equations, which are subsequently non dimensionalized and discretized in rectangular domain. The effect of nanoparticle volume fraction values on velocity, temperature and concentration profiles are discussed.
Keywords: Nanofluid; straight stretching surface; mixed convection; finite volume method